On homotopy nilpotency of the octonian plane $\mathbb{O}P^2$ - Golasi´nski, Marek (MATHEMATICA SCANDINAVICA, 2021)
Let $\mathbb{O}P^2_{(p)}$ be the $p$-localization of the Cayley projective plane $\mathbb{O}P^2$ for a prime $p$ or $p=0$. We show that the homotopy nilpotency class $nil Ω(\mathbb{O}P^2_{(p)})<∞ $ for $p>2$ and $nil Ω (\mathbb{O}P^2_{(p)})=1$ for $p>5$ or $p=0$. The homotopy nilpotency of remaining Rosenfeld projective planes are discussed as well.